2007
DOI: 10.1021/jp0722760
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-Dependent Hydration at Micellar Surface:  Activation Energy Barrier Crossing Model Revisited

Abstract: In recent years, the validity of the activation energy barrier crossing model at the micellar surface brings notable controversy (Sen, P.; Mukherjee, S.; Halder, A.; Bhattacharyya, K. Chem. Phys. Lett. 2004, 385, 357-361. Kumbhakar, M.; Pal, H. J. Phys. Chem. B 2004, 108, 19246-19254.) in the literature. In order to check the validity of the model by time-resolved solvation of a probe fluorophore, a wider range of temperature must be considered. At the same time, spatial heterogeneity (solubilization) of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
78
1
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(88 citation statements)
references
References 38 publications
8
78
1
1
Order By: Relevance
“…The same group has recently reported 13 the temperature-dependent solvation dynamics of coumarin dyes in aqueous triblock copolymer micelles in the temperature range 293-343 K and interpreted their results in view of structural and hydration studies. Temperature-dependent solvation dynamics of a fluorophore DCM (4-(dicyanomethylene)-2-methyl-6(p-(dimethylamino)-styryl)-4H-pyran) in SDS micelle have been recently reported from our group, 14 and the study revealed a good agreement with the Arrhenius type behavior within the framework of overall structural integrity of the micelle.…”
Section: Introductionsupporting
confidence: 57%
“…The same group has recently reported 13 the temperature-dependent solvation dynamics of coumarin dyes in aqueous triblock copolymer micelles in the temperature range 293-343 K and interpreted their results in view of structural and hydration studies. Temperature-dependent solvation dynamics of a fluorophore DCM (4-(dicyanomethylene)-2-methyl-6(p-(dimethylamino)-styryl)-4H-pyran) in SDS micelle have been recently reported from our group, 14 and the study revealed a good agreement with the Arrhenius type behavior within the framework of overall structural integrity of the micelle.…”
Section: Introductionsupporting
confidence: 57%
“…The increased compressibility of hydration water at higher temperatures is also observed at the interface of anionic sodium dodecyl sulfate (SDS) micelles. 17 The observations suggest that both the rigidity and the number of bound waters in the interfacial hydration shell are lost at higher temperatures. The hydration shell, thus, becomes soft at higher temperatures.…”
Section: Resultsmentioning
confidence: 99%
“…This leaves us with the choice of biomimetics such as SDS micelles 17 and AOT/isooctane/water reverse micelles, 18 which retain their structural integrity over a wide range of temperatures 17 to serve as model biointerfaces. Instances of replacing a complicated biomolecule by more…”
Section: Introductionmentioning
confidence: 99%
“…The recent advancement in the field of nanoscience requires the preparation of bioactive nanoparticles under different temperatures using protein molecules as templates. [86][87][88][89] The single-residue mutations could modify the stability of albumin and that the effects are more pronounced for mutations in sub domain IIA (sudlow site I) than for mutations in sub domain IIIA (sudlow site II). Similar approach was being made to characterize the simultaneous binding of the ligands in various temperaturedependent folded states of HSA for revealing the nature of binding of ligands.…”
Section: Conformational Changes Affecting Ligand Bindingmentioning
confidence: 99%